Penile Rehabilitation after Pelvic Cancer Surgery. (15th February 2015) - Aoun, Fouad; Peltier, Alexandre; Velthoven, Roland van
Abstract : Erectile dysfunction is the most common complication after pelvic radical surgery. Rehabilitation programs are increasingly being used in clinical practice but there is no high level of evidence supporting its efficacy. The principle of early penile rehabilitation stems from animal studies showing early histological and molecular changes associated with penile corporal hypoxia after cavernous nerve injury. The concept of early penile rehabilitation was developed in late nineties with a subsequent number of clinical studies supporting early pharmacologic penile rehabilitation. These studies included all available phosphodiesterase type 5 inhibitors, intracavernosal injection and intraurethral use of prostaglandin E1 and to lesser extent vacuum erectile devices. However, these studies are of small number, difficult to interpret, and often with no control group. Furthermore, no studies have proven an in vivo derangement of endothelial or smooth muscle cell metabolism secondary to a prolonged flaccid state. The purpose of the present report is a synthetic overview of the literature in order to analyze the concept and the rationale of rehabilitation program of erectile dysfunction following radical pelvic surgery and the evidence of such programs in clinical practice. Emphasis will be placed on penile rehabilitation programs after radical cystoprostatectomy, radical prostatectomy, and rectal cancer treatment. Future perspectives are also analyzed.